PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN PENGETAHUAN KESIAPSIAGAAN SISWA DALAM MENGHADAPI BENCANA ALAM - Lukman, Syahril; Hi. Muhammad, Hujairah (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
Volcanic eruption disasters are a real threat to people living in disaster-prone areas of Mount Gamalama. In an effort to mitigate disaster risk, disaster education in schools is one of the most important preventive strategies. This study aims to determine the application of the role-playing learning model to improve students' knowledge of preparedness in facing the eruption of Mount Gamalama. The method used is classroom action research (CAR) which is carried out in two cycles, with the research subjects being grade XI students of SMA Negeri 5 Kota Ternate. The instrument used is a questionnaire. Each cycle consists of planning, implementation, observation, and reflection. The results of the study showed that there was a significant increase in students' knowledge of preparedness after the application of the role-playing learning model. In cycle I, the percentage of students who achieved the Minimum Mastery Criteria (KKM) was 32%. After improving learning in cycle II, the percentage of completion increased to 92%. This increase shows that the role-playing learning model can improve students' knowledge of preparedness in facing the eruption of Mount Gamalama Ternate.